Unraveling the potential of endothelial progenitor cells as a treatment following ischemic stroke - Custodia, Antía; Ouro, Alberto; Sargento-Freitas, João; Aramburu-Núñez, Marta; Pías-Peleteiro, Juan Manuel; Hervella, Pablo; Rosell, Anna; Ferreira, Lino; Castillo, José; Romaus-Sanjurjo, Daniel; Sobrino, Tomás (Frontiers in Neurology, 2022)
Ischemic stroke is becoming one of the most common causes of death and disability in developed countries. Since current therapeutic options are quite limited, focused on acute reperfusion therapies that are hampered by a very narrow therapeutic time window, it is essential to discover novel treatments that not only stop the progression of the ischemic cascade during the acute phase, but also improve the recovery of stroke patients during the sub-acute or chronic phase. In this regard, several studies have shown that endothelial progenitor cells (EPCs) can repair damaged vessels as well as generate new ones following cerebrovascular damage. EPCs are circulating cells with characteristics of both endothelial cells and adult stem cells presenting the ability to differentiate into mature endothelial cells and self-renew, respectively. Moreover, EPCs have the advantage of being already present in healthy conditions as circulating cells that participate in the maintenance of the endothelium in a direct and paracrine way. In this scenario, EPCs appear as a promising target to tackle stroke by self-promoting re-endothelization, angiogenesis and vasculogenesis. Based on clinical data showing a better neurological and functional outcome in ischemic stroke patients with higher levels of circulating EPCs, novel and promising therapeutic approaches would be pharmacological treatment promoting EPCs-generation as well as EPCs-based therapies. Here, we will review the latest advances in preclinical as well as clinical research on EPCs application following stroke, not only as a single treatment but also in combination with new therapeutic approaches.